The oligodendroglial precursor cell line Oli-neu represents a cell culture system to examine functional expression of the mouse gap junction gene connexin29 (Cx29) - Söhl, Goran C.; Hombach, Sonja; Degen, Joachim; Odermatt, Benjamin (Frontiers in Pharmacology, 2013)
The potential gap junction forming mouse connexin29 (Cx29) protein is concomitantly expressed with connexin32 (Cx32) in peripheral myelin forming Schwann cells and together with both Cx32 and connexin47 (Cx47) in oligodendrocytes of the CNS. To study the genomic structure and functional expression of Cx29, either primary cells or cell culture systems might be selected, from which the latter are easier to cultivate. Both structure and expression of Cx29 is still not fully understood. In the mouse sciatic nerve, brain and the oligodendroglial precursor cell line Oli-neu the Cx29 gene is processed in two transcript isoforms both harbouring a unique reading frame. In contrast to Cx32 and Cx47, only Cx29 protein is abundantly expressed in undifferentiated as well as differentiated Oli-neu cells but the absence of Etbr dye transfer after microinjection concealed the function of Cx29 mediated gap junction communication between those cells. Although HeLa cells stably transfected with Cx29 or Cx29-eGFP neither demonstrated any permeability for Lucifer yellow nor for neurobiotin, blocking of Etbr uptake from the media by gap junction blockers does suppose a role of Cx29 in hemi-channel function. Thus, we conclude that, due to its high abundance of Cx29 expression and its reproducible culture conditions, the oligodendroglial precursor cell line Oli-neu might constitute an appropriate cell culture system to study molecular mechanisms or putative extracellular stimuli to functionally open Cx29 channels or hemi-channels.